2011
DOI: 10.1074/jbc.m110.149880
|View full text |Cite
|
Sign up to set email alerts
|

Tamm-Horsfall Glycoprotein Interacts with Renal Outer Medullary Potassium Channel ROMK2 and Regulates Its Function

Abstract: Tamm-Horsfall glycoprotein (THGP) or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
95
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 41 publications
7
95
0
2
Order By: Relevance
“…The mechanisms by which defective trafficking of mutant uromodulin leads to hyperuricemia are uncertain, but defective urine concentrating ability suggests a mechanism linked to volume contraction (5). This hypothesis is supported by a reduced TAL sodium reabsorption in uromodulindeficient mice (11,12).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The mechanisms by which defective trafficking of mutant uromodulin leads to hyperuricemia are uncertain, but defective urine concentrating ability suggests a mechanism linked to volume contraction (5). This hypothesis is supported by a reduced TAL sodium reabsorption in uromodulindeficient mice (11,12).…”
Section: Introductionsupporting
confidence: 56%
“…Recent findings have shed light on the physiologic role of uromodulin (20), including studies in knockout mice evidencing a link between uromodulin and regulation of sodium transport in the TAL (11,12) as well as previous data showing that uromodulin expression increases with salt intake in animal models (21).…”
Section: Introductionmentioning
confidence: 99%
“…24 Recently, it was found that UMOD had an effect on the renal outer medullary potassium channels (ROMK2), and thus increased salt reabsorption along the TAL. 7 According to these findings, it appeared that UMOD excretion may induce changes in sodium reabsorption in the TAL, thus influencing sodium reabsorption in the proximal tubules as well. Because UMOD may be involved in the regulation of sodium reabsorption, it is reasonable to hypothesize that UMOD influences BP.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, it is found that UMOD has an effect on renal outer medullary potassium channels and thus regulate salt reabsorption along the thick ascending limb. 7 Furthermore, in a genome-wide association study, one of the common variants of UMOD, rs13333226, is identified as being associated with HTN and cardiovascular risk in European cohorts. 8 We therefore systematically genotyped common variants across the UMOD gene in a community-based cohort and explored whether common variants of the UMOD gene are associated with BP.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that uromodulin in the polymerized form contributes to the water impermeability of TAL [5]. In addition, uromodulin increases membrane expression of the renal outer medullary potassium channel (ROMK2) and activates the TAL N-K-2Cl co-transporter in vitro [12,13]. Disruption of these pathways may contribute to the mild salt and water wasting seen in UMOD mutations, but this remains to be studied.…”
Section: Functions Of Uromodulinmentioning
confidence: 99%